Az Osztrák–Magyar Monarchia politikai földrajzi helyzete a Nagy Háború előestéjén - Nagy, Miklós Mihály (Közép-Európai Közlemények, 2017)
During the decades preceding the outbreak of World War I, the Habsburg Empire, which was reorganized as the Austro-Hungarian Empire in 1867, used to be a dominant force within European power relations, although it was not considered a real world power. Still, due to its geographical dimensions, potential and its position in the European continent, it was a political geographical factor whose existence and later lack thereof had to be taken into consideration in international politics. The Austro-Hungarian Empire embodied the state of “In-between Europe”, even though states with large dimensions had existed in this region in previous centuries. The present study describes the political geographical situation of this Danube empire, emphasizing that the spatial structure of this multi-national empire had evolved over centuries and had formed a uniform economic region, and it was its multi-national diversity that caused its downfall. The spatial development of the Austro-Hungarian Empire having evolved from the Habsburg Empire was a continuation of previous processes. The main feature of these processes is that this Danube empire preserved its historically western character but its spatial development shifted eastwards in contrast to other Western European countries, who had turned their historical fronts westward since the discovery of the American continent. As a result, the Austro-Hungarian Empire developed another historical front on the East, and, thus became “two-fronted”.